Protein synthesis during somatic embryogenesis of moon orchid Phalaenopsis amabilis (L.) Bl. - EDY SETITI WIDA UTAMI; ISSIREP SOEMARDI; TARYONO TARYONO; ENDANG SEMIARTI (Society for Indonesian Biodiversity, 2007)
Research to analyse protein synthesis during somatic embryogenesis of moon orchid Phalaenopsis amabilis (L.) Bl has been carried out. One year old of plantlets were used as explants sources. Basal leaf of these explants were cultured in medium New Phalaenopsis (NP) added with 2mg/L NAA during 1 day (P1), 2 days (P2), 4 days (P3), 6 days (P4), 8 days (P5). The explants were cultured in medium NP without NAA were used as control, during 1 day (K1), 2 days (K2), 4 days (K3), 6 days (K4), 8 days (K5). Analysis of the protein synthesiswas observed by electrophoresis using SDS-PAGE method according to Maniatis et al. (1982). The measuring of protein bands used the densitometer. To detect the specific protein which possible function in controlling embryogenesis by comparing profiles of leaf protein which cultured at NP media added NAA and without NAA. The analyses of protein profile were done at the culture of day 1, 2, 4, 6 and 8 after inoculating. Result of the research indicated that a protein of 14 kDa was detected in the explants were cultured in medium NP added NAA only, and it was not detected in explants were cultured in medium NP without NAA. This protein probably embryonic protein has a function to control embryogenic callus initiation. A protein of 16 kDa was detected in the explants were cultured in medium NP added NAA and without NAA. This protein is possibly siklin has a function to regulation of cells proliferation during embryogenesis.Â© 2007 Jurusan Biologi FMIPA UNS SurakartaKey words: Phalaenopsis amabilis (L.) Bl, protein synthesis, SDS-PAGE